Emerging Roles of Liquid–Liquid Phase Separation in Cancer: From Protein Aggregation to Immune-Associated Signaling - Lu, Jiahua; Qian, Junjie; Xu, Zhentian; Yin, Shengyong; Zhou, Lin; Zheng, Shusen; Zhang, Wu (Frontiers in Cell and Developmental Biology, 2021)
Liquid–liquid Phase Separation (LLPS) of proteins and nucleic acids has emerged as a new paradigm in the study of cellular activities. It drives the formation of liquid-like condensates containing biomolecules in the absence of membrane structures in living cells. In addition, typical membrane-less condensates such as nuclear speckles, stress granules and cell signaling clusters play important roles in various cellular activities, including regulation of transcription, cellular stress response and signal transduction. Previous studies highlighted the biophysical and biochemical principles underlying the formation of these liquid condensates. The studies also showed how these principles determine the molecular properties, LLPS behavior, and composition of liquid condensates. While the basic rules driving LLPS are continuously being uncovered, their function in cellular activities is still unclear, especially within a pathological context. Therefore, the present review summarizes the recent progress made on the existing roles of LLPS in cancer, including cancer-related signaling pathways, transcription regulation and maintenance of genome stability. Additionally, the review briefly introduces the basic rules of LLPS, and cellular signaling that potentially plays a role in cancer, including pathways relevant to immune responses and autophagy.